Late onset of cerebellar cortical degeneration in a Magellanic penguin (Spheniscus magellanicus) - IOANNIDIS, Marianthi (J Vet Med Sci, 2019)
An 8-year-old female Magellanic penguin (Spheniscus magellanicus) started to show epilepsy-like seizures. Subsequent magnetic resonance imaging (MRI) examinations did not reveal any responsible lesions. The neurological symptoms worsened at the age of 10. This penguin became recumbent and died 6 months later after the apparition of the recumbency. At necropsy, only multiple yellowish necrotic lesions in the air sacs and lungs were found. Histopathological evaluation of the brain showed a marked loss of Purkinje cells and many hypertrophied parvalbumin-positive basket/stellate cells were seen in the cerebellar cortex. Calbindin immunohistochemistry demonstrated disrupted arrangement of dendrites in the Purkinje cells. This case was diagnosed as cerebellar cortical degeneration with a very late onset and a slow progression in a Magellanic penguin.